Analisis Literasi Multimodal Buku Cerita Anak Bergambar Sebagai Upaya Pemilihan Bahan Ajar Membaca Permulaan Siswa Sekolah Dasar - Indah Nurmahanani (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Illustrated children's story books are a construction of the world, a perspective that is the result of processing and reading by the creator of the book on other texts he consumes. Picture story books are a medium to offer a view of how the world should be seen and understood. In relation to picture story books, children who are the readers of the stories conveyed in this book will very likely have views of the world around them as views offered by picture story books. Therefore, children and parents should be equipped with the ability to read critically the message conveyed by this picture story book. They must have abilities that allow them not only to be able to critically read narrative texts but also understand how to read pictures, as a mode that appears with verbal texts in storybooks. Multimodal literacy is defined as the knowledge and skills that children must possess, especially, in critically reading verbal texts and especially visual texts. Through this multimodal literacy analysis, it is hoped that we can interpret the messages conveyed by picture story books for elementary school students